Sonic hedgehog promotes generation and maintenance of human forebrain Olig2 progenitors - Ortega, Juan Alberto; Radonjic, Nevena V.; Zecevic, Nada (Frontiers in Cellular Neuroscience, 2013)
Function of oligodendrocytes (OLs), myelin forming cells in the CNS, is disrupted in demyelinating diseases such as periventricular leukomalacia or multiple sclerosis. It is, thus, important to better understand factors that can affect generation or differentiation of human OLs. In rodents, Sonic hedgehog (Shh) is influencing expression of Olig2, a helix-loop-helix transcription factor required for development of OLs. In humans, Olig2 is present in cortical progenitors at midgestation, however the role of Shh in the specification of human OLs, including Olig2 positive (Olig2+) progenitors, is not fully understood. Here we studied in vitro effects of Shh signaling on proliferation and specification of human cortical Olig2+ progenitors at midgestation. First, we established that the spatiotemporal pattern of Olig2 expression in the human developing CNS, described on cryosections, was preserved in mixed and enriched radial glia cell (RGC) cultures. Next, we demonstrated that in vitro treatment with Shh induced an increase in the number of Olig2+ progenitors. Shh treatment increased the density of early oligodendrocyte progenitors (OPCs) at the expense of radial glia cells, while the number of late OPCs, did not change. However, inhibition of endogenous Shh with cyclopamine did not reduce the density of Olig2+ cells, implying the presence of an additional Shh-independent mechanism for OLs generation in vitro. These results suggest that the primary role of Shh signaling in the human dorsal oligodendrogenesis is the expansion and specification of multipotent radial glia progenitors into Olig2+ early OPCs. These results obtained in vitro are relevant to understand primary myelination during CNS development, as well as remyelination in demyelinating diseases.